Contact load is associated with both contact and non-contact injuries in rugby union - Iwasaki, Yusuke; Someya, Yuki; Nagao, Masashi; Aoyagi, Masashi; Shiota, Yuki; Takazawa, Yuji (Frontiers in Physiology, 2025)
ObjectiveManaging matches and training loads is crucial for injury prevention. Contact load is a defining feature of rugby union, and World Rugby has proposed its management as a key strategy for the prevention of injuries. In fact, increased contact load has been associated with a higher incidence of injuries. However, the specific relationship between contact load and the occurrence of both contact and non-contact injuries remains unclear. In this study, we aimed to clarify the association between contact load and the occurrence of contact and non-contact injuries in elite rugby union players.MethodsSixty-six elite male rugby union players (age: 26.5 ± 3.5 years) in Japan were monitored over three seasons. Contact load, an indicator of training load, was evaluated based on collision count and collision load, measured using a global positioning system device. For each player, cumulative contact loads were calculated using time windows of 1, 2, 3, 4, 5, 6, 7, 14, 21, and 28 days. The association between contact load and injury incidence (contact and non-contact) was analyzed using generalized estimating equations.ResultsA total of 193 injuries were recorded. Of these, 136 were contact injuries and 57 were non-contact injuries. The contact load was significantly associated with both types of injury. For contact injuries, the highest odds ratio for the collision count was observed on day 1 and gradually decreased toward day 7 (day 1: odds ratio, 2.10 [95% confidence interval: 1.67–2.64]; day 7: 1.31 [1.15–1.48]). The odds ratio for collision load also declined from days 1–7 (day 1: 3.27 [2.18–4.90]; day 7: 1.44 [1.17–1.78]). By contrast, non-contact injuries showed a different pattern. For collision count, the highest odds ratio was observed on day 2 and then gradually decreased toward day 4 (day 2: 1.38 [1.04–1.83]; day 4: 1.35 [1.06–1.72]). The odds ratio for collision load was also the highest on day 2 and decreased toward day 4 (day 2: 1.75 [1.16–2.65]; day 4: 1.56 [1.07–2.27]).ConclusionContact load was associated with both contact and non-contact injuries in elite rugby union players.